New Developments in Non-allergen-specific Therapy for the Treatment of Food Allergy - Long, Andrew; Borro, Matteo; Sampath, Vanitha; Chinthrajah, R. Sharon (Current allergy and asthma reports, 2020)
Purpose of Review The prevalence of food allergy is increasing. At the current time, there are no approved treatments for food allergy. Major limitations of immunotherapy are long treatment periods (months or years), frequent clinic visits, high costs, increased risk of adverse events during treatment, and lack of durability of desensitization. Additionally, it is allergen-specific, and in those allergic to multiple allergens, the length and cost of treatment are further increased. In this review, we summarize recent developments in novel non-allergen-specific treatments for food allergy. Recent Findings A number of monoclonal antibodies that block IgE or specific pro-allergenic cytokines or their receptors have shown promise in clinical trials for food allergy. Summary The insight we have gained through the use of one drug for the treatment of an atopic disease is quickly being translated to other atopic diseases, including food allergy. The future for food allergy treatment with biologics looks bright.